Dual‐band circular‐polarization filter for obliquely incident light. Issue 10 (27th July 2016) - Erten, Sema; Lakhtakia, Akhlesh
ABSTRACT: Chiral sculptured thin films of zinc selenide with different helical periods were deposited on both sides of a glass slide using the serial bideposition technique in order to fabricate a dual‐band circular‐polarization filter polarizer that exhibits two distinct circular Bragg regimes for a wide range (about 45°) of the angle of incidence. This device can be angle tuned within a ±8% spectral range. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:2381–2384, 2016